FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERNIKAHAN USIA DINI PADA REMAJA PUTRI - Afiah Afiah; Syafriani Syafriani; Erlinawati Erlinawati (Jurnal Doppler, 2021)
The highest cases of early marriage in Kampar Regency are in Kuok sub-district, amounting to 128 cases of early marriage from 234 marriages or around 54.70%. Marriage can be influenced by several factors including knowledge, adolescent environment, adolescent education, family income, parental education, and parental occupation. The purpose of this study was to analyze the relationship between knowledge, adolescent environment, adolescent education, family income, parental education and parental occupation with the incidence of early marriage in Kuok Village in 2021. The design of this study was analytic with a Cross Sectional design. The sampling technique in this research is Simple Random Sampling. This research was conducted on 16 – 22 June 2021 in Kuok Village with a sample of 77 marriages. Analysis of the data used is univariate and bivariate. The results of the bivariate analysis based on the Chi Square test showed that the p value of knowledge with a value of 0.039